2015
DOI: 10.1002/hyp.10596
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological resilience of a Canadian Rockies headwaters basin subject to changing climate, extreme weather, and forest management

Abstract: Abstract:Marmot Creek Research Basin in the Canadian Rockies has been the site of intensive streamflow, groundwater, snow accumulation, precipitation, and air temperature observations at multiple elevations. The basin was instrumented in 1962, subjected to forestry experiments in the mid-1970s, and experienced extreme flooding in 2013. Climate change, forest cover change, and recent extreme weather make the basin an ideal laboratory for studying hydrological resilience. Observations show increases in low eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 59 publications
5
89
2
1
Order By: Relevance
“…The mountains range in elevation from 1600 to 2800 m, and typical mountain environments include montane and subalpine forest cover, alpine tundra, and talus/rock at higher elevation. The climate is characterized by cool, wet summers and long, cold winters; monthly mean air temperature ranges from −10.7 • C in January to 11.7 • C in July (Pomeroy et al, 2012;Fang et al, 2013;Harder et al, 2015). There is a significant difference in the annual precipitation from 638 mm at the valley bottom to 1100 mm at higher elevations (Storr, 1967).…”
Section: Sites and Datamentioning
confidence: 99%
“…The mountains range in elevation from 1600 to 2800 m, and typical mountain environments include montane and subalpine forest cover, alpine tundra, and talus/rock at higher elevation. The climate is characterized by cool, wet summers and long, cold winters; monthly mean air temperature ranges from −10.7 • C in January to 11.7 • C in July (Pomeroy et al, 2012;Fang et al, 2013;Harder et al, 2015). There is a significant difference in the annual precipitation from 638 mm at the valley bottom to 1100 mm at higher elevations (Storr, 1967).…”
Section: Sites and Datamentioning
confidence: 99%
“…Conversely, in the eastern slopes of the Rocky Mountains, Marmot Creek, AB, has shown considerable resilience in its flow regime. Despite winter warming, declining low-elevation snowpacks, forest cover reduction, and, more recently, extreme weather, streamflow volume, timing, and magnitude of peak have not changed since 1962 (Harder et al, 2015). An increase in the fraction of precipitation occurring in spring and the frequency of multiple-day rainfall events may have counteracted warmer conditions and lower snowpacks at low elevations.…”
Section: Insights On Change From the Wecc Observatoriesmentioning
confidence: 99%
“…These results are consistent with increased snow accumulation in the clearings and varying melt rates with more prolonged melt for smaller clearings, particularly those facing north ). These differences did not translate into detectable impacts at the Marmot Creek basin scale (Harder et al 2015).…”
Section: Variables Measured (2004-2016)mentioning
confidence: 87%
“…Later analyses of the pre-and post-treatment streamflow by Harder et al (2015) showed that after treatment, there was a trend for earlier and more variable streamflow and decreased peak flow at Cabin Creek, and less variable flow at Twin Creek when compared to the Middle Creek control. These results are consistent with increased snow accumulation in the clearings and varying melt rates with more prolonged melt for smaller clearings, particularly those facing north ).…”
Section: Variables Measured (2004-2016)mentioning
confidence: 99%
See 1 more Smart Citation